Properties of Malaysian fired clay bricks and their evaluation with international masonry specifications - a case study - Arman Ali, Zainab (2005)
The research examined and assessed the properties of Malaysian fired clay bricks to provide information for the development and revision of Malaysian Standard MS 76:1972. Some laboratory investigations on bricks were conducted in conjunction with the use of various masonry standards to evaluate the compressive strength, dimensional tolerances, water absorption, initial rate of suction, efflorescence, density and soluble salt content. The test methods were mostly based on MS 76:1972 and BS 3921:1985 and in some cases new testing approaches were adopted to assess new property requirements not catered in existing masonry specifications. The analysis on random samples indicated the acceptance of the use of a normal probability theory even for data with values of coefficient of variation close to 30%. In the case where the coefficient of variation exceeded 30 % the lognormal probability function applies. The statistical control charts traced data homogeneity for the population and data lying beyond the 5 % confidence limit, which were not accounted for in the analysis. The compressive strengths of facing bricks ranged from about 40 N/mm2 to 50 N/mm2 with lower values for common bricks, i.e. 30 N/mm2 to 40 N/mm2. These ranges of compressive strengths fall in the top range specified in Singapore Standard, SS 103:1974. The compressive strengths specified in ASTM were based on dry curing whilst British Standard, Singapore Standard and Malaysian Standard were tested in saturated conditions. Curing methods affect compressive strength with air curing giving higher values. Water absorption for the bricks under investigation range from 10 % to 12 % and therefore do not fit in the category of Engineering A or B of MS 76:1972 and BS 3921:1985, however satisfy the requirements for the categories of SW (severe weathering) bricks in ASTM. The dimensions satisfy the tolerances given in BS 3921:1985 except for the height. However, the dimensional tolerance fits the T1 category of the European Standard EN 771-1. The initial rate of suction for the bricks ranged from 1.4 to 2.0 kg/min/m2 indicating high suction property thus implying the necessity of wetting bricks before laying. Efflorescence does not seem to be a major problem hence these bricks could be satisfactorily used for facing construction purposes without resulting in salt deposition on the surfaces. The range of density (1760 to 1800 kg/m3) exhibited by the bricks satisfy the sound insulation requirements specified in the United Kingdom Building Regulations. In this research a method of predicting the compressive strength of bricks when laid in the different orientations was derived. This is a useful means of estimating the compressive strength of brick in practice where test are only conducted on the bed face. The research also highlighted a method of estimating the porosity of bricks for values of known water absorption.